2013
DOI: 10.1155/2013/310186
|View full text |Cite
|
Sign up to set email alerts
|

Dietaryω-3 Polyunsaturated Fatty Acid DHA: A Potential Adjuvant in the Treatment of Cancer

Abstract: ω-3 Polyunsaturated fatty acids (PUFAs), mainly present in fish oil, are part of the human diet. Among PUFAs, docosahexaenoic acid (DHA) has received particular attention for its anti-inflammatory, antiproliferative, proapoptotic, antiangiogenetic, anti-invasion, and antimetastatic properties. These data suggest that DHA can exert antitumor activity potentially representing an effective adjuvant in cancer chemotherapy. This review is focused on current knowledge supporting the potential use of DHA for the enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 99 publications
1
103
0
3
Order By: Relevance
“…Omega-3 fatty acids have been considered potentially useful for adjuvant cancer therapy according to their properties on antitumor activity: anti-inflammatory, anti-proliferative, pro-apoptotic, anti-invasion, anti-metastatic and epigenetic regulation [4e6]. Accordingly, tumor cell response may be modified via multiple mechanisms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 fatty acids have been considered potentially useful for adjuvant cancer therapy according to their properties on antitumor activity: anti-inflammatory, anti-proliferative, pro-apoptotic, anti-invasion, anti-metastatic and epigenetic regulation [4e6]. Accordingly, tumor cell response may be modified via multiple mechanisms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that EPA and DHA fatty acids have antioxidant properties and play a vital role in free radical metabolism. 38 These effects occur partly via activation of Peroxisome proliferator-activated receptors (PPARs) by n-3 polyunsaturated fatty acids in fish oil. 39 Previous study reported that PPARγ is an important factor in the regulation of PON1 expression, and in neutralizing oxidative stress.…”
mentioning
confidence: 99%
“…NSAIDs in breast and pancreatic cancer-The idea of using NSAIDs in breast cancer is not exactly new, as many studies use aspirin and other NSAIDs or even precursors of resolution inflammation mediators, such as PUFA including DHA as chemopreventive agents against breast cancer [62,63]. In fact, regular use of aspirin and possibly other NSAIDs seem to decrease breast cancer risk [64], while ibuprofen exerts a protective but marginal effect regarding recurrence [65].…”
Section: Nsaidsmentioning
confidence: 99%